Inorganic Colloidal Electrolyte for Highly Robust Zinc-Ion Batteries - Gao, Jiawei; Xie, Xuesong; Liang, Shuquan; Lu, Bingan; Zhou, Jiang (Nano-Micro Letters, 2021)
Zinc-ion batteries (ZIBs) is a promising electrical energy storage candidate due to its eco-friendliness, low cost, and intrinsic safety, but on the cathode the element dissolution and the formation of irreversible products, and on the anode the growth of dendrite as well as irreversible products hinder its practical application. Herein, we propose a new type of the inorganic highly concentrated colloidal electrolytes (HCCE) for ZIBs promoting simultaneous robust protection of both cathode/anode leading to an effective suppression of element dissolution, dendrite, and irreversible products growth. The new HCCE has high Zn2+ ion transference number (0.64) endowed by the limitation of SO42−, the competitive ion conductivity (1.1 × 10–2 S cm−1) and Zn2+ ion diffusion enabled by the uniform pore distribution (3.6 nm) and the limited free water. The Zn/HCCE/α-MnO2 cells exhibit high durability under both high and low current densities, which is almost 100% capacity retention at 200 mA g−1 after 400 cycles (290 mAh g−1) and 89% capacity retention under 500 mA g−1 after 1000 cycles (212 mAh g−1). Considering material sustainability and batteries’ high performances, the colloidal electrolyte may provide a feasible substitute beyond the liquid and all-solid-state electrolyte of ZIBs. Highlights: 1 The Zn/MnO2 cell with inorganic colloidal electrolyte demonstrates unprecedented durability over 1000 cycles. 2 For the cathode, the presence of the protective film can inhibit the dissolution of manganese element and the formation of irreversible by-products. 3 For the anode, it can reduce the corrosion and de-solvation energy, inhibit the growth of dendrite and irreversible by-products.